ESTADO CONFESIONAL EN COSTA RICA: ALGUNOS DEBATES DESDE LA CONSTRUCCIÓN DE POLÍTICAS PÚBLICAS - Carballo Villagra, Priscilla (Universidad de Costa Rica, 2019)
This is a synthetic presentation of the political, ideological, legal and historical basis of the Costa Rican state’s funding to the Catholic Church, and also the funding amounts assigned to the church from five institutional mechanism under study. The field work consisted in reviewing institutional documents and interviewing officials in the respective institutions. The main conclusion of the work is that this relationship of exchange of gifts between the church and the state is based on a process of ritualization-blessing of political power, however, it is necessary to broaden the debate on the channeling of these funds as a debate of public policy.